Community-Based Routine Road Maintenance as a Strategy to Mitigate Social Inequality in Provincial Road Networks - Yudi Sekaryadi; Wimpy Santosa; Caroline Sutandi; Anan Anisarida; Ida Farida (Equivalent: Jurnal Ilmiah Sosial Teknik, 2026)
Background: Road infrastructure development plays a crucial role in fostering economic growth and improving interregional connectivity. However, uneven distribution of benefits can generate or intensify existing social disparities. Objective: This study aims to analyze the role of community-based routine provincial road maintenance in mitigating social inequality by evaluating maintenance implementation and assessing community participation patterns. Methods: This study employs a mixed-methods quantitative-evaluative design across 20 provincial road sections in nine districts of West Java Province. Data were collected from 89 respondents for the routine maintenance variable and 140 respondents for the community participation variable. Results: The evaluation results indicate that all routine maintenance variables fall within moderate to excellent categories, except for the labor factor, which scored poorly (1.65) due to limited availability of certified skilled workers. For community participation, all variables scored moderate to excellent, except the willingness to contribute financially (1.83), largely influenced by low household income. SEM analysis identifies significant variables including shoulder damage level, labor factor, community attendance in meetings, and participatory contributions. Conclusion: The study concludes that social disparities can be mitigated by increasing community income through operational cooperation between government and villages, enabling communities to participate in routine maintenance—particularly in simple tasks requiring trained local labor.